A field study of spatial preferences in enterprise microblogging. (June 2016) - Recker, Jan; Lekse, Dominik
How does the introduction of enterprise social networking affect the way that geographically dispersed managers communicate with each other? We examine enterprise social network (ESN) usage data obtained from a community of store managers in a leading Australian retail organization, over a period of 15 months after introduction of the platform. Our interest in examining this data is in spatial communication preferences by the network users, that is, to ascertain who is communicating with whom and where. Our analysis of 12, 000 messages exchanged between 530 managers shows that interactions can generally be characterized by individual preferences for local communication but also that two different user communities exist - 'locals' and 'globals'. We develop empirical profiles for these two types of social network user communities, and we compare the empirical results against contrasting theoretical perspectives for spatial preference patterns in communication behaviour. We outline implications for theories on spatial influences on communication behaviours on ESNs.